Impact of heat stress and nutritional interventions on poultry production. Issue 4 (17th December 2018) - HE, S.P.; AROWOLO, M.A.; MEDRANO, R.F.; LI, S.; YU, Q.F.; CHEN, J.Y.; HE, J.H.
Abstract : High ambient temperatures affect animal production and welfare in tropical and sub-tropical regions of the world. Feed intake, growth rate, mortality, egg production, hatchability and other production traits related to the economic success of the poultry industry are adversely affected by severe heat stress. In general, heat stress induces the activity of the neuroendocrine system, resulting in activation of the hypothalamic-pituitary-adrenal (HPA) axis, and elevated corticosterone (CORT) concentrations, which affects metabolism and immune responses. These include negative regulation of metabolic hormones, antibody production and heterophil to lymphocyte (H/L) ratio. Heat stress increases mitochondrial activity, causing reactive species overproduction which disrupts the antioxidant balance, leading to oxidative stress damage of membranes, protein and DNA. Heat stress stimulates the central nervous system (CNS), which significantly reduces daily gain, feed intake and FCR in poultry. Consequently, from an animal husbandry perspective, intervention strategies to relieve heat stress conditions have been the focus of many published studies. This review describes the effect of high temperature on production, behavioural, biochemical and immune responses, including oxidative damage that occur during heat stress in poultry, in broilers and laying hens. Moreover, nutritional interventions to alleviate the negative consequence of heat stress is discussed.